Bending Behavior of Corroded H-Shaped Steel Beam in Underground Environment - Jie Sheng; Junwu Xia; Hongfei Chang (Applied Sciences, 2021)
To investigate the residual bending strength of a corroded H-shaped steel beam in an underground coal mining environment, the law governing the degradation of the mechanical properties of corroded steel was first investigated through tensile testing. Subsequently, a four-point bending test was conducted on corroded H-shaped steel beams. The influence of the corrosion rate and sustained loading ratio on the residual bending performance of a corroded H-beam was investigated. The results reveal that the uniform corrosion and uneven corrosion of the steel occurred simultaneously. Additionally, pits with a small size appeared on the steel surface and the number of these pits increased with the corrosion time. Four different fracture modes were observed after the tensile test, and the yield strength and ultimate strength of the corroded steel decreased as the corrosion rate increased. In the bending test, the failure mode of the corroded H-shaped steel beam was not changed by the corrosion. The bearing capacity, stiffness, and ductility of the corroded H-shaped steel beams decreased with the increase in the corrosion rate, and the sustained loading further decreased the bearing capacity. Finally, a simple method for assessing the yield load and ultimate load of corroded H-shaped steel beams is proposed.